Advances in the design of a multipurpose fragment screening library. (June 2013) - Wilde, Felix; Link, Andreas
<x xml:space="preserve">Abstract</x> Introduction: Fragment-based lead discovery (FBLD) has evolved from an emerging technology to a state-of-the-art approach in drug research. The efficacious use of fragment libraries for the discovery of hits and generation of lead structures has to an increasing extent become implemented both within academia and the pharmaceutical industry but the careful or optimal selection of appropriate fragments remains a demanding task, especially when fragments are intended for the lead generation in more than one or even diverse and difficult targets. Areas covered: Progress in non-commercial screening collections of fragment-like compounds for multiple screening purposes deposited at academic institutions is reviewed as well as approaches for the generation of slim and shapely novel platforms for diversity. Recent literature on multipurpose fragment screening libraries and the papers presented at the EFMC-ISMC meeting in Berlin in August 2012 have been taken into account. Expert opinion: Existing fragment libraries tend to focus on sp2-rich compounds covering well-explored areas of chemical space. In order to improve the quality of the hits and to be able to tackle seemingly undruggable targets, flat scaffolds should be replaced by shapely molecular cores dominated by sp3 hybridization. Structurally novel fragments are needed and in this respect, the role of halogen bonds has been underestimated. Pooling strategies for fragment cocktails must be designed to detect simultaneous binding of weak ligands in close proximity: cooperative binding is too important to rely on chance discoveries.